Penerapan Building Information Modelling (BIM) Dalam Pemodelan Dan Penjadwalan Pada Proyek Pembangunan Masjid Al-Muttahidin Payakumbuh - Widiawan, Aswad Ari; Hidayat, Benny (Jurnal Bangunan, Konstruksi & Desain, 2025)
This study discusses the application of Building Information Modeling (BIM) to the Al-Muttahidin Mosque construction project in Payakumbuh, which was built on the land of an existing mosque. The complexity of this project requires a planning strategy that takes into account safety, scheduling, and coordination between demolition and construction work. Modeling was carried out using Autodesk Revit 2023 to create 3D models of the old and new buildings, then analyzing the work sequence through integration with Microsoft Project and 4D simulation using Autodesk Navisworks Manage. The results show that BIM modeling facilitates the identification of design conflicts, work sequence planning, and construction activity duration estimation. The project requires 39 work items with a total duration of 201 days, of which the existing mosque cannot be used for 54 days due to safety aspects. This study confirms that BIM plays a significant role in improving scheduling efficiency, minimizing the risk of construction conflicts, and supporting the visualization of the project implementation process.